Prospects of Improvement of Civil Liability Norms for Participants in Corporate Relations - KUANYSHBAYEVA, Saule; BEKIMBETOV, Tugel; SARTBAYEVA, Uldanay; MEIRKULOVA, Gulmira; TUREGELDIYEV, Bakdaulet (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).18, 2019)
The purpose of the study is an in-depth consideration of the grounds and the procedure for taking a civil action against participants in corporate relations. Modern corporate relations in the Republic of Kazakhstan have emerged relatively recently and are on the rise, which necessitates the constant attention of a lawmaker striving to protect the rights of all corporation members. Individual participants of corporate relations often perform illegal and bad-faith actions and use their powers for profiteering thus inflicting financial losses upon other participants. To thwart such activities, one must employ various types of liability for offenders, including civil liability. The article shows that many issues of civil liability regulation within corporate relations are not sufficiently adjusted, which affects the operation of corporations and the protection of participants’ rights and facilitates the abuse of power. The scientific novelty of the results obtained is attributable to the fact that the article is aimed at complex research into the legal aspects of corporate relations regulation in Kazakhstan. The main possible solutions to the problems highlighted are presented in the article. The practical significance of the study is that the results can be used in both science and research, as well as lawmaking. Namely, scientifically, they can be used to further develop the theoretical concept of corporate liability, while the recommendations can be used in lawmaking, during the process of improving the legislation of Kazakhstan and other countries facing similar problems in the field of regulating issues related to liability in corporate law.